DETERMINATION OF DISEASE DEVELOPMENT IN PLANTS ON THE BASIS OF PROGNOSIS - Rasulova Madina Shukhratovna; Khidoyatova Dilorom Mirshakhabovna (Western European Studies, 2024)
Determining the development of diseases in plants based on prognosis is widely used in modern agricultural technologies. This approach is based on a variety of data to predict the occurrence and spread of plant diseases. The article describes the types of forecasting and the stages of the forecasting scheme one by one
Keywords: prognosis; destruction; pathogen